Cranial trepanation and healing process in modern patients—Bioarchaeological and anthropological implications. Issue 6 (25th June 2020) - Partiot, Caroline; Lepetit, Aliénor; Dodré, Emilie; Jenger, Camille; Maureille, Bruno; Liguoro, Dominique; Thomas, Aline
Abstract: The diagnosis of cranial trepanation in the archaeological record has always been a big challenge for archaeologists. The identification is first and foremost based on the shape and edges of the opening, and in cases where the individual survived, the shape and edges resulted from both the surgical procedure and the healing process. Because of the lack of reliable data on the osseous remodelling process of the skull, it is difficult to distinguish true trepanations from some pathological or physiological defects called pseudotrepanations. Furthermore, it is challenging to investigate the post‐operative survival time. The purpose of this paper was to summarize observations made on a total of 90 archaeological samples of cranial lesions interpreted as 'partially' or 'completely' healed trepanations, and compare them with 14 modern case studies. Observations made on monitoring post‐operative scans of modern patients, at varying times after craniotomy, provided a preliminary timetable for the successive post‐surgery bony changes in the skull, and confirmed that the process of osseous remodelling does lead to smooth and rounded edges of the profile of the opening. However, contrary to what has been observed in several archaeological case studies, none of the cases shows a complete closure of the cranial vault. The sharp vertical edges of the opening become bevelled at late stages of healing, which has to be taken into consideration when interpreting the procedures and methods in past population. By bridging bioarchaeology and medical sciences, this study adds to previous discussions on the diagnosis of healed trepanation in the archaeological record, by providing detailed descriptions of morphological changes at various healing stages, that may help archaeologists to identify ancient trepanations more accurately. Abstract : We investigated the macroscopic healing processes of the cranial vault based on CT scanning records of modern patients, in order to improve the positive and differential diagnosis of trepanations in archaeological samples. Our results have demonstrated how the inclination of the edges of a healed trepanation may be related to the healing process, and not only to the cranial opening technique, which now has to be taken into consideration when interpreting the procedures in past population.